TISSUE DOPPLEROGRAPHY IN EARLY DIAGNOSIS OF FUNCTIONAL MYOCARDIAL DISORDERS IN ARTERIAL HYPERTENSION - Y. A. Vasyuk; A. B. Hadzegova; S. V. Ivanova; E. N. Yuschuk; I. M. Amirbegishvili; N. I. Gerasimova (Столичная издательская компания, 2016)
Aim. To determine the potential of tissue Dopplerography (TDG) for early diagnosis of functional myocardial disorders in patients with arterial hypertension (HT).Material and methods. 66 patients with HT were examined. Clinical examination, 24-hour ambulatory blood pressure monitoring, two-dimensional- and Doppler-echocardiography of transmitral blood flow, TDG of mitral annulus, determination of blood level of brain natriuretic peptide (BNP) were performed.Results. Regional disturbances of diastolic myocardial function are detected in patients with HT and normal transmitral blood flow. These disturbances are more expressed in left ventricle (LV) remodeling. The LV remodeling is also connected with disorders of the longitudinal myocardial contractile systolic function of the inferior wall. These disorders are more expressed in patients with HT and chronic heart failure (CHF). The average ratio of peak rates of the early transmitral blood flow and the diastolic myocardial movement (E/Ea), as well as the average level of BNP confirmed the moderate increase in end-diastolic pressure in LV.Conclusion. Regional disorders of diastolic myocardial function in patients with HT are detected before structural changes of LV even in normal transmitral blood flow. The LV remodeling is related to the disorders of diastolic and regional systolic myocardial function, which are accompanied with increase in BNP level. At the same time increased BNP level is especially related with increased E/Ea ratio, which is more earlier predictor of CHF in hypertensive patients.